Volume 1: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-53225
|View full text |Cite
|
Sign up to set email alerts
|

Computational Parametric Study of Fuel Distribution in an Experimental Trapped Vortex Combustor Sector Rig

Abstract: Numerical simulations are performed to predict the flow properties in a liquid spray droplets fueled Trapped Vortex Combustor (TVC) sector rig. The quantities studied include aerodynamics, pressure drop, spray droplets trajectories, evaporation, mixing and combustion, and combustor exit temperature distributions. Previous numerical simulations of this TVC configuration have identified basic flow patterns and performance characteristics, and were generally in good agreement with experimental data. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This configuration employed struts to obtain better mixing in the mainstream. Meyer et al [3] and other similar inverstigations [4,5,6] conceptualised the TVC for an annular combustor. A two-dimensional, dual cavity rig was designed and tested.…”
Section: Introductionmentioning
confidence: 99%
“…This configuration employed struts to obtain better mixing in the mainstream. Meyer et al [3] and other similar inverstigations [4,5,6] conceptualised the TVC for an annular combustor. A two-dimensional, dual cavity rig was designed and tested.…”
Section: Introductionmentioning
confidence: 99%
“…It was developed by the Air Force Research Laboratory and General Electric Aircraft Engines in the U.S. [3,4] , and has been widely studied for aircraft engine applications [5][6][7] , recently also for stationary gas turbine combustor applications as well [8,9] . Detailed experimental tests have demonstrated that trapped vortex combustor has extraordinary performances, such as high combustion efficiency, low NOx emission, reduced lean blow out, increase in altitude re-light, and so on [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The drag induced on the flow by a cavity has been thoroughly studied in the literature, it was found that the optimal cavity length in terms of drag reduction is associated with the appearance of quasi-stable vortices within the cavity [9,10], linked with a pseudo-stagnation of the shear layer at the downstream cavity corner [11,12]. On these grounds, various TVC (Trapped Vortex Combustor) have been discussed and studied [8,13,14].…”
Section: Introductionmentioning
confidence: 99%